1986
DOI: 10.1002/pola.1986.080240210
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of O‐methacryloyl ketone oxime‐methyl mechacrylate copolymers in the solid phase

Abstract: SynopsisSeveral kinds of copolymers bearing 0-acyloxyimino groups were prepared and their photodegradabilities were examined. Copolymers of 0-methacryloyl ketone (acetophenone, benzophenone, or 2-acetonaphthone) oxime and methyl methacrylate (or styrene) were photodegradable even in the solid phase but in the case of copolymers of 0-acryloyl acetophenone oxime and methyl methacrylate (or styrene) both photodegradation and photocrosslinking were observed. From these results it was found that the photodegradabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Therefore, the degradabilities of the polymer films parallel those of the polymer solutions. We also found that increasing the irradiation temperature (up to 100°C) facilitated the main‐chain scission and retarded the crosslinking,17 which may be due to the increased chain mobility 15…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Therefore, the degradabilities of the polymer films parallel those of the polymer solutions. We also found that increasing the irradiation temperature (up to 100°C) facilitated the main‐chain scission and retarded the crosslinking,17 which may be due to the increased chain mobility 15…”
Section: Resultsmentioning
confidence: 65%
“…The oxidation of tertiary alkyl radicals in the main chain would hinder the β‐scission predominantly occurring in PBMA. The alkyl radicals formed in PBA, through side‐chain degradation and hydrogen abstraction or other processes, would react with oxygen to produce hydroperoxide and finally carbonyl groups, which could initiate the photooxidative scission of the main chain 8, 10, 12, 15. It is noteworthy that oxygen facilitates the main‐chain scission of the PBMA film as well as the PBA one and diminishes their crosslinking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their structures and characteristics are shown in Fig. 1 and Table 1, respectively. 0-Acryloyl acetophenone oxime (AAPO) and 0-acryloyl 2-acetonaphthone oxime (AANO) were prepared by reaction of the corresponding oximes with acryloyl chloride by a method similar to that described in a previous article (14). Styrene (St) and ethyl acrylate (EA) were purified by distillation under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…2 [5]. Tsunooka and Suyama studied the photodegradation of copolymers of MMA and 0-(methacyloyl acetophenone oxime [6]; moreover, using NMR spectra, they clarified the main chain degradation mechanism via the tertiary polymer radical resulting from the photoirradiation of a copolymer of styrene with 0-(methacyoyl)acetophenone oxime [7].…”
Section: Introductionmentioning
confidence: 99%